The Application Of Medication And Strategies For The Implementation Of Hallucinations In Tn. S (Terra Neutral Separated) With A Nursing Diagnosis Of Sensory Perception Disorders (Hallucinations) - Risdiyanto, Nugeraha; Wahyuni, Uni; Wulandari, Afni; Nur Azmi, Nadila; Puspita Sari , Melati (Riviera Publishing, 2024)
Hallucinations are sensory perception disorders that attack the five senses, where a person perceives an object or image and thoughts that do not occur or are not real. Hallucinations include sound, sight, taste, touch, or smell sensations without real stimulus. Treatment for patients with hallucinations is by identifying the type of hallucination, applying medication, and implementing strategies to distract or overcome the hallucinations experienced. The objectives of this study include (1) Describing problems regarding sensory perception disorders and (2) Describing and implementing nursing care in cases of mental disorders with a medical diagnosis of schizophrenia at Soerojo Hospital Magelang. This study uses a qualitative approach with case studies as the primary method, using observation sheets, interviews, and documentation studies. The subject of this study used one patient, Mr S, who had a nursing diagnosis of sensory perception disorders at RSD Soerojo Hospital Magelang. Nursing care for patient Mr S with a diagnosis of sensory perception disorder (hallucinations) in this case showed success as indicated by the signs and symptoms experienced by the patient decreasing. After four days of intervention, the patient was able to overcome hallucinations by scolding, interacting with the surrounding environment, and taking care of himself by bathing and dressing more neatly.